Honey, I Shrunk the Guests Page Access Tracking using a Minimal Virtualisation Layer - Nguyen, Dustin Tien; Rußer, Sebastian; Ott, Maximilian; Kapitza, Rüdiger; Schröder-Preikschat, Wolfgang; Nolte, Jörg (4th Workshop on Heterogeneous Composable and Disaggregated Systems, 2025)
Advances in memory-intensive areas such as machine learning and graph processing drive demand for suited memory technologies. Part of the answer lies in multi-memory architectures with fast and high-capacity memory tiers. Heterogeneous systems can be very diverse, ranging from NUMA to persistent memory and CXL-attached memory. Efficient usage requires support from the operating system (OS) with knowledge of memory performance characteristics and detailed insight into the page access behaviour of processes. Gathering statistics on the read/write-ratio of accesses and (huge) page utilisation is expensive with common methods. In this paper, we propose vmmload, a minimal virtualisation layer to monitor user space programs using a virtualisation-based page modification log (PML) for efficiently gathering runtime statistics. While PML is a hardware extension that was originally designed to track virtual machine memory access, vmmload enables observation of individual processes. vmmload monitored user space processes run with PML-enabled virtualisation, but are still able to interface with the host OS. We explore the viability of using PML without a conventional virtual machine and providing the host OS with the ability to use these extensions directl